1998
DOI: 10.1046/j.1365-2141.1998.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of an association between chlamydial infections and malignant lymphomas

Abstract: Chronic infections may predispose to malignant growth. Recently, serological markers of chronic Chlamydia pneumoniae infection have been associated with lung cancer. Our aim was to study the possible association between chronic chlamydial infections and malignant lymphomas. The present case-control study involved 72 patients with lymphoma (31 females and 41 males) and matched controls. 53 patients had non-Hodgkin's lymphoma (NHL) and 19 had Hodgkin's disease. The sera, collected at the time of diagnosis, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 36 publications
1
14
0
3
Order By: Relevance
“…One study in a HIV-positive population reported no association with sexually transmitted infections (17), but others have produced conflicting results possibly due to confounding by HIV infection (18,19). Only one study tested for serologic evidence of a sexually transmitted infection (20); this small hospital-based case-control study showed a significant positive association between non-Hodgkin lymphoma and Chlamydia trachomatis antibodies detected by ELISA but not when the more specific microimmunofluorescence method was used.…”
Section: Discussionmentioning
confidence: 99%
“…One study in a HIV-positive population reported no association with sexually transmitted infections (17), but others have produced conflicting results possibly due to confounding by HIV infection (18,19). Only one study tested for serologic evidence of a sexually transmitted infection (20); this small hospital-based case-control study showed a significant positive association between non-Hodgkin lymphoma and Chlamydia trachomatis antibodies detected by ELISA but not when the more specific microimmunofluorescence method was used.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Chlamydia have been associated with lymphoproliferative disorders in adults [31,32]; in particular, ocular lymphomas have been linked to Chlamydia psittaci [33]. On the contrary, it is believed that there is no convincing proof for association between Chlamydia and leukaemia [34].…”
Section: Cholangiocarcinoma Cholangiocarcinomamentioning
confidence: 99%
“…and Mycoplasma pneumoniae can cause chronic pulmonary diseases such as chronic bronchitis and adult-onset asthma (Bjornsson et al, 1996;Daian et al, 2000), and chronic infection with C. pneumoniae or M. pneumoniae has been linked to an increased risk of lung cancer (Pehlivan et al, 2004;Littman et al, 2005). C. pneumoniae and C. trachomatis infections, particularly the former, are also associated with an increased risk of lymphoma although their specific association with pulmonary MALT lymphoma is unclear (Anttila et al, 1998). The present study was thus designed to examine the potential association of Chlamydiae and Mycoplasma infection with pulmonary MALT lymphoma.…”
mentioning
confidence: 99%